The emerging multifunctional roles of ERAP1, ERAP2 and IRAP between antigen processing and renin-angiotensin system modulation - Mattorre, Benedetta; Tedeschi, Valentina; Paldino, Giorgia; Fiorillo, Maria Teresa; Paladini, Fabiana; Sorrentino, Rosa (Frontiers in Immunology, 2022)
The Endoplasmic Reticulum Aminopeptidase 1 and 2 (ERAP1 and ERAP2) and Insulin Regulated Aminopeptidase (IRAP) are three M1 zinc metalloproteases whose role in antigen processing is the refining of peptidome either in the Endoplasmic reticulum (ERAP1 and ERAP2), or in the endosomes (IRAP). However, other novel and distinct functions are emerging. Here, we focus specifically on ERAP2. This gene has a peculiar evolutionary history, being absent in rodents and undergoing in hu-mans to a balanced selection of two haplotypes, one of which not expressing the full length ERAP2. These observations suggest that its role in antigen presentation is not essential. An additional, less in-vestigated role is in the regulation of the Renin Angiotensin System (RAS). ERAP1 and ERAP2 cleave Angiotensin II (Ang II) into Ang III and IV, which counteract the action of Ang II whereas IRAP is itself the receptor for Ang IV. We have recently reported that macrophages, independently from the haplotype, express and release a N-terminus ERAP2 “short” form which directly binds IRAP and the two molecules are co-expressed in the endosomes and on the cell membrane. This new evidence suggests that the maintenance of the ERAP2 gene in humans could be due to its activity in the regulation of the RAS system, possibly as an Ang IV agonist. Its role in the immune-mediated diseases as well as in disorders more specifically related to an imbalance of the RAS system, includ-ing hypertension, pre-eclampsia but also viral infections such as COVID-19, is discussed here.